Intra-banking competition in Ecuador: new evidence using panel data approach. Issue 50 (10th June 2020) - Solano, Javier; Camino-Mogro, Segundo; Armijos-Bravo, Grace
Abstract : Purpose: Banks are institutions that inject money in the economy and help to boost it when there are problems in some markets, especially in productive sectors. In this way, analysing the competition in this sector is an important tool for policymakers as non-competitive behaviour could affect the financial system and economy. The purpose of this paper is to measure the degree of competition in the Ecuadorian private banking sector divided by size, from 2000 to 2015, using panel data collected by the official regulator institution. Design/methodology/approach: The authors applied the model proposed by Panzar and Rosse (1987) and its H -statistic using a reduced price and revenue equation estimated by pooled ordinary least squares, fixed effects, random effects, feasible generalised fixed effects and panel correction standard errors (PCSE). Findings: The authors show that given the presence of some problems in data such as heteroskedasticity and autocorrelation, the most appropriate technique is PCSE. The authors also found robust evidence supporting that large banks compete in a monopolistic market, small and medium-sized banks operate in monopolistic competition, and Ecuadorian small, medium-sized and large banks stay in long-run equilibrium. Originality/value: This paper contributes to the actual literature of competition degree in two ways. First, different from traditional papers, we do not control by size; so, we divided the analysis by size, because in Ecuador and also in many developing countries, bank's competition is different for each group of size because the levels of liquidity, risk and other indicators are different from one group to another. Second, we show the robustness of the results using a scaled and unscaled equation, using many controls and using five methods to contrast the competition degree.